Talent Management Strategies as a Key to Innovation: Exploring Diversity in Yogyakarta's MSMEs - Yunus Agung Kristanto; Sudarto Sudarto; Najmudin Najmudin (International Journal of Economics, Business and Innovation Research, 2024)
Abstract This study explores the crucial role of talent management strategies in fostering innovation within Micro, Small, and Medium Enterprises in Yogyakarta, Indonesia, with a specific focus on diversity as a driving factor. Employing a mixed methods approach, the research highlights the limited awareness among Yogyakarta's MSME actors regarding the significance of talent management and its impact on business innovation, particularly through leveraging diversity. The findings indicate a positive correlation between the implementation of talent management strategies and enhanced business innovation among MSMEs in the Malioboro area of Yogyakarta. Notably, diversity as a mediating variable strengthens the positive relationship between talent management and business innovation. This underscores the urgency for MSMEs to adopt inclusive talent management strategies that value diversity to stimulate innovation and competitiveness.